A Tool to Create Assurance Case through Models - Utsunomiya, Hiroyuki; Kobayashi, Nobuhide; Morisaki, Shuji; Yamamoto, Shuichiro (Transactions on Engineering and Computing Sciences, 2018)
In this paper, an assurance case development tool is proposed to derive the argument decomposition structure from generic model definitions. The method solves O-DA issues for assuring business, application, and technology architecture of TOGAF. An example case study using the proposed tool is also shown for the system configuration model of the tool itself. Discussions based on the case study showed the effectiveness and appropriateness of the proposed methods. Future work includes the formalization of assurance case derivation process from ArchiMate, UML, and SysML models.